DEVELOPMENT OF ANDROID-BASED HEALTHY LIFESTYLE PHYSICAL EDUCATION LEARNING MEDIA TO INCREASE STUDENT UNDERSTANDING - Oman Unju Subandi; Yasep Setiakarnawijaya; Sudrajat, Deni (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This research aims to develop interactive learning media to help students understand healthy lifestyle behaviour in physical education for D-phase students in class VII and Evaluate the Effectiveness of Learning Media to evaluate how effective interactive learning media can help students understand healthy lifestyle behaviours in Physical education phase-D Class VII.This type of research is a development Research and Development (R&D) through quantitative methods. This method was determined based on data collection techniques carried out during the product development process. Through this research using the ASSURE model and has six stages ; Analyze Learner, State Objectives, Select methods, media, and materials, Utilize media and materials, Require learner participation, Evaluate and Revise.. The findings of this study were piloted with seventh grade junior high school students in Serang and Pandeglang districts. Based on random sampling technique, four junior high schools were obtained. The subjects in the small-scale test were 31 students and the large-scale test was 60 students and the research sample was 36 students.The results of this research are in the form of an android application as an interactive multimedia for healthy lifestyles. The mean result is 0.5617 which means it is included in the medium group. Based on the results of the analysis, it can be concluded that the learning media for physical education sports and health material on healthy lifestyles based on android for junior high school class VII is effective for increasing students understanding of sports and health subject matter, with an average pre-test score of 47.77 and an average post-test score of 77.00. Based on results in the conclusion that this Android-based interactive learning media for physical education is good or feasible enough for students.